The impact of soil and water conservation on agricultural economic growth and rural poverty reduction in China - Abdul Rahim, Abdul Samad; Sun, Chenglong; A. W., Noraida (MDPI, 2018)
There is a lack of systematic study on the impact of soil and water conservation on the sustainable development of agricultural economies and rural poverty reduction in China. This study investigates the effects of soil and water conservation on agricultural economic growth. It looks at levels of disposable income in rural households in China and uses the econometric method to examine panel data obtained from 30 provinces between 2003–2012. Agricultural gross domestic product (GDP) is the dependent variable, and soil and water conservation are the independent variables. Farmland area, along with four other variables, is the control variables that are used to establish the Cobb–Douglas production function and provide further data. It was found that soil and water conservation have a significant impact on the per capita income of rural households in China. The findings support that soil and water conservation can contribute to the agricultural economic growth and rural poverty reduction in China. There is evidence that supports the idea that soil quality and capital input are now more important in poverty reduction and economic growth than farmland area and agricultural labour. The government and farmers need to prioritise investment in soil and water conservation in order to promote the development of agricultural economies and reduce rural poverty.